The Principle of Audi et Alteram Partem in the Process of Proof in Criminal Cases (Analysis of Decision No. 123/PID.B/2022/PN YYK - Hartanto, Hartanto; Susanto, Susanto; Alimpeev, Daniil (Universitas Negeri Gorontalo, 2024)
This research examines the application of the audi et alteram partem principle by the panel of judges in case Number 123/Pid.B/2022/PN Yyk, focusing on how it influenced the judicial decision-making process. The audi et alteram partem principle, which ensures that both parties in a trial have an equal opportunity to present their arguments and evidence, is central to ensuring justice and fairness in legal proceedings. However, this study finds that the principle was not fully applied in this case, leading to an imbalance in the trial. The research combines normative and empirical methods, including interviews and literature reviews, to explore whether the evidence presented was adequately considered according to the Criminal Procedure Law. Findings suggest that the judges' failure to properly apply this principle resulted in a decision that did not meet the required standard of balance or fairness, ultimately weakening the defendant's position. This research highlights the urgent need for judicial reforms to strengthen adherence to procedural fairness, ensuring that legal decisions reflect the facts of the case and the fundamental principles of justice. The study contributes to the broader understanding of how judicial practices affect the fairness of criminal trials in Indonesia, offering recommendations for improving the application of legal principles in future cases.